الإجارة المنتهية بالتمليك بين المعايير الشرعية للأيوفي والقانون المدني البحريني :دراسة شرعية قانونية = Ijārah Al-Muntahiyyah Bi Al-Tamlīk between AAOIFI Shariah standards and Bahraini Civil Law: a shariah and legal study - Alshaikh, Hamad Farooq; Zakariyah, Habeebullah (Usuli Faqih Research Centre PLT., 2024)
The research sheds light on the provisions of Ijarah Muntahia Bittamleek as a formula for financing real estate from Islamic banks to clients, in comparison between the positive Bahraini law and the Sharia standards of the Accounting and Auditing Organization for Islamic Financial Institutions (AAOIFI). The research aims to clarify the most important points of agreement and disagreement between the civil law and Sharia standards with regard to Islamic financial transactions to identify the size of the gap between them in preparation for conducting more studies in this regard because the financial transactions applied in Islamic banks in the Kingdom of Bahrain are subject to Sharia standards on the one hand and the provisions of the civil law on the other. The researcher relied on the qualitative approach and the comparative evaluative analytical description. The researcher reached points of disagreement and agreement between local laws and the Sharia standard, where there was complete agreement between them by 54%, partial agreement by 13%, and contradiction by 13%, while there are some points that were touched upon in one source without the other by 20%. The researcher found that 70% of the points of conflict between them can be reconciled without fundamental changes, and that the most important difference between them is the interest in late payment. The researcher recommends conducting more studies on the most important differences between local laws and Sharia standards and re-conducting a comprehensive study of Sharia standards to examine the gaps and weaknesses through which Islamic banks and their contracts may be affected. The researcher also recommends preparing an independent law for banks in general and Islamic banks in particular to ensure addressing problems that may arise, in addition to the importance of covering the shortage of specialized cadres in the judiciary